EU HTA Regulation and Joint Clinical Assessment—Threat or Opportunity? - Volker Schuster (Journal of Market Access & Health Policy)
The vision of a unified European HTA is by no means a new endeavor. At its core are the publicly declared ambitions to harmonize assessments of clinical data within the EU and avoid the duplication of efforts. Not surprisingly, these ambitions are publicly announced to be motivating the new 2022 EU HTA regulation. However, industry experts typically see more of a risk for additional bureaucracy resulting in delays, further scrutiny, and one additional EU (clinical) dossier to submit on top of all national HTA dossiers, which could be considered a duplication of effort and therefore counterproductive. Regardless of how the details of the process will be defined and how the entire process will work in practice, we can be sure that EU officials will refer to the EU HTA and Joint Clinical Assessment (JCA) in particular as a learning system. The purpose of this article is to take a closer look at the new EU HTA regulation and analyze threats and opportunities for manufacturers and what the resulting opportunities and threats will be at the affiliate level throughout the EU.